Estimating leakage from forest carbon sequestration programs - Brian C. Murray; Bruce A. McCarl; Heng-Chi Lee (The University of Western Ontario, Department of Economics, 2003)
Leakage from forest carbon sequestrationthe amount of a program's direct carbon benefits undermined by carbon releases elsewheredepends critically on demanders' ability to substitute non-reserved timber for timber targeted by the program. Analytic, econometric, and sector-level optimization models are combined to estimate leakage from different forest carbon sequestration activities. Empirical estimates for the U.S. show leakage ranges from minimal (<10 percent) to enormous (>90 percent), depending on the activity and region. These results suggest that leakage effects should not be ignored in accounting for the net level of greenhouse gas offsets from land use change and forestry mitigation activities.
Keywords: Q23; Q24; 330; forestry; climate change mitigation; land use change